Valorização da madeira Eucalyptus sp. via pirólise: caracterização e rendimentos dos produtos - Silva, Felipe Thalles Moreira (2019)
The growth of global energy demand, coupled with factors such as the vulnerability of the supply of fossil fuels in a scenario of mitigation of environmental impacts, has motivated humanity to search for clean and renewable energy sources. In this context, biomass presents itself as a viable resource of great interest. Largest charcoal producer in the world, Brazil has a well-developed forestry sector, as well as being one of the main producers of wood in the world. A large fraction of this production is destined for the steel industry in the production of charcoal. However, only 30% of all the energy presented in the wood is turned into charcoal, the other 70% consisting of condensable and non-condensable gases emitted into the atmosphere generating pollution and waste of energy. In this sense, the present study aims to evaluate different thermochemical processes, slow, fast pyrolysis and micro pyrolysis in order to ascertain the potentialities of the products generated. The slow pyrolysis, or carbonization, was carried out in a muffle furnace, with the objective of charring the species Eucalyptus urograndis, where the physical-chemical characterization of charcoal, bio-oil and non-condensable gases (NCG) generated by the process. The behavior of some variables (heating rate and final temperature) that affect the charcoal production process through a factorial design (3k) was also analyzed. The average yield of charcoal, bio-oil and NCG reached positive values about 32.6%, 40.1% and 27.3%, respectively. The experimental results showed that the charcoal from the clone evaluated can be considered, in general, homogeneous in physical and chemical aspects and presented satisfactory characteristics for the production of charcoal for steel use. The composition of the bio-oil was investigated and it was observed that the bio-oil from carbonization is rich mainly in phenolic compounds and organic acids. Fast pyrolysis was performed with the same biomass in a fluidized bed reactor at 550°C in order to characterize the products obtained and also, the micro pyrolysis or analytical pyrolysis was carried out to investigate and understand the characteristics of the generated vapors. Analytical pyrolysis tests were performed at 380°C, 430°C and 480°C. The specific objective in this context is to compare the composition of the vapors generated in the analytical pyrolysis of the Eucalyptus urograndis species using a commercial micro-pyrolyzer with the composition of the bio-oil produced in an experimental unit in a fast pyrolysis fluidized bed reactor. The average yields of the fast pyrolysis products were: 25.2% bio-oil, 15.5% char and 59.3% non-condensable gases. The main components of the bio-oil were identified in the GC / MS and the bio-oil from the fast pyrolysis showed aldehyde and phenolic compounds. The pyrolytic vapors presented with the increase in temperature an increase in the formation of phenols, ketones, ethers, alcohols and a reduction of esters and aldehydes. Organic acids did not have a tendency, though, were the major compounds found in the bio-oil. In this way, these bio-oils can be used as an alternative source of value-added chemicals for various applications. In parallel, carbonations of endocarp of palm trees (coconut macauba endocarp and babassu coconut) were carried out in order to evaluate the potentiality of these materials, as well as their physicochemical characterizations of coal and bio-oil.